Komunikasi Pemasaran Pakaian Adat Bali Melalui Facebook Bagi Pelaku UMKM di Kota Mataram - Febriyani, Ida Ayu Indah (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relations, 2025)
The existence of online marketing can help in promoting and marketing products offered to the entire community. Similar to marketing carried out by Balinese traditional clothing traders, Facebook is used to market their products. This study aims to produce a form of marketing communication for Balinese traditional clothing through Facebook for effective MSMEs in Mataram City, identify and analyze the inhibiting factors for the use of Facebook in marketing communication for Balinese traditional clothing for MSMEs in Mataram City and find and analyze solutions to the obstacles to the use of Facebook in marketing communication for Balinese traditional clothing for MSMEs in Mataram City. The results of the study indicate that the effective forms of marketing communication for Balinese traditional clothing through Facebook in Mataram City are advertising, sales promotion, public relations & publicity and personal selling. The inhibiting factors faced are physical barriers, semantic barriers, obstacles can also come from internal barriers, process barriers originating from the message sender. The solution to overcome the obstacles of using Facebook in marketing communication of Balinese traditional clothing for MSMEs in Mataram city is to provide all the facilities needed for online marketing, for example the availability of wifi or the use of a starter card that has a strong internet network, using the right language, creating another account, consumers coming directly to the location of the Balinese traditional clothing shop, using the right language, coming directly to the shop location, conducting training, namely photography training.